2010
DOI: 10.1007/s11906-010-0171-x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Damage and Regeneration: The Role of the Renin-Angiotensin-Aldosterone System

Abstract: The renin-angiotensin-aldosterone system (RAAS) is part of the blood pressure regulating system. Its main effector peptide is angiotensin II (Ang II). Although it may induce hypertension, the proinflammatory, profibrotic, and prothrombotic effects are mainly mediated by effects of Ang II on the cellular and molecular level that are independent of blood pressure. Therefore, pharmacotherapeutic intervention within the RAAS is an important treatment modality for patients suffering from cardiovascular diseases, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 55 publications
0
26
0
2
Order By: Relevance
“…It has been suggested that AngII-induced mesangial cell contraction with efferent arteriolar vasoconstriction initiates intraglomerular hypertension and may lead to enhanced matrix formation and renal fibrosis after increased synthesis of TGF-β 50 . Several studies have shown that angiotensin II type 1 receptor blockers (ARBs), are particularly effective to reduce proteinuria through their direct action on AT1R-expressing cells in endothelium and vascular smooth muscle expressing the receptor 51, 52 . Therefore blocking the renin-angiotensin-aldosterone system would be beneficial beyond its effect on blood pressure 52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that AngII-induced mesangial cell contraction with efferent arteriolar vasoconstriction initiates intraglomerular hypertension and may lead to enhanced matrix formation and renal fibrosis after increased synthesis of TGF-β 50 . Several studies have shown that angiotensin II type 1 receptor blockers (ARBs), are particularly effective to reduce proteinuria through their direct action on AT1R-expressing cells in endothelium and vascular smooth muscle expressing the receptor 51, 52 . Therefore blocking the renin-angiotensin-aldosterone system would be beneficial beyond its effect on blood pressure 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that angiotensin II type 1 receptor blockers (ARBs), are particularly effective to reduce proteinuria through their direct action on AT1R-expressing cells in endothelium and vascular smooth muscle expressing the receptor 51, 52 . Therefore blocking the renin-angiotensin-aldosterone system would be beneficial beyond its effect on blood pressure 52 . For example, the glomerular efferent arteriole is particularly sensitive to angiotensin II 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Although a vasoconstrictor, Ang II induces endothelial damage by inhibiting endothelial cells regeneration. Ang II acts as a second messenger to activate intracellular signaling pathways such as mitogen-activated protein kinase (MAPK) and AKT, pathways that mediate cell proliferation and apoptosis and thereby vascular dysfunction [51]. Ang II plays a significant role in the initiation and progression of atherogenesis, an inflammation mediated process.…”
Section: Raas and Vascular Inflammationmentioning
confidence: 99%
“…These include: Platelet-Derived Growth Factor (PDGF), Epidermal Growth Factor (EGF), Transforming Growth Factor beta (TGF-β) and Insulin-like Growth Factor 1 (IGF-1) g and may contribute to the tissue fibrogenesis properties of the RAS [12]. Activation of NADPH oxidase pathway and stimulation of ROS production in different cell types is another major downstream of AT1 stimulation [5].…”
Section: The Classical Ras Axis Of Regulationmentioning
confidence: 99%